MULTILINGUALISM IN EDUCATION: AN ANALYSIS OF THE IMPACT OF LOCAL LANGUAGES ON THE MASTERY OF INDONESIA LANGUAGE LEARNING IN ELEMENTARY SCHOOL - Rijni Rahmatullah; Sri Suryaningsih; Try Supryanto (Universitas Majalengka, 2025)
Indonesian has a strategic role in the world of education as the main language of instruction as well as a means of developing students' cognitive and character. However, the reality at SDN Teta, Lambitu District, shows that students' mastery of Indonesian is still low due to the dominant use of Lambitu and Bima languages ​​in daily interactions. This study aims to analyze the impact of the use of regional languages ​​on mastery of Indonesian language material and the multilingual learning strategies implemented by teachers. The research uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, documentation studies, and focus group discussions (FGD). The findings reveal that local languages play a positive role in improving students’ mastery of the Indonesian language subject at SDN Teta. The results of the study showed that students had difficulty understanding academic vocabulary, sentence structure, and Indonesian pronunciation, but the use of regional languages ​​actually helped understanding the material through translanguaging and code switching strategies. Teachers utilize a contextual approach based on local culture so that students are more active and involved in learning. In addition, parental support and school policies also play a role in optimizing bilingual strategies in the classroom. In conclusion, regional languages ​​play a dual role, namely as an obstacle because they give rise to linguistic interference, but at the same time, they are an effective bridge towards mastering Indonesian. This study emphasizes the importance of an integrative, contextual, and inclusive multilingual approach in improving the quality of Indonesian language learning in multilingual areas.